Dance education in Singapore: Policy, discourse, and practice. Issue 1 (2nd January 2018) - Chua, Joey
ABSTRACT: This article provides an overview of dance education in schools in Singapore with regard to physical education, co-curricular activity, initiatives by the National Arts Council's Arts Education unit, and pre-tertiary and tertiary dance programs. In an effort to gain a better understanding of how well the official discourse and the reality of schooling in dance interconnect, a meta-analysis of published articles, conference papers, committee reports, and curricula was conducted. Situated within the larger sociocultural, political, and historical contexts, Singapore presents a curious case for probing the merits and limitations of research, policy initiatives, and policy implementation. In the conclusion, the author argues that the development of a coherent dance education in Singapore requires "fixing" three dilemmas—meritocratic schooling in dance, the ill-defined and exhaustive use of the term "talent, " and the uneven research that has not kept pace with the policy initiatives.